2017
DOI: 10.1136/bmjgh-2016-000182
|View full text |Cite
|
Sign up to set email alerts
|

Impact of a malaria intervention package in schools onPlasmodiuminfection, anaemia and cognitive function in schoolchildren in Mali: a pragmatic cluster-randomised trial

Abstract: BackgroundSchool-aged children are rarely targeted by malaria control programmes, yet the prevalence of Plasmodium infection in primary school children often exceeds that seen in younger children and could affect haemoglobin concentration and school performance.MethodsA cluster-randomised trial was carried out in 80 primary schools in southern Mali to evaluate the impact of a school-based malaria intervention package. Intervention schools received two interventions sequentially: (1) teacher-led participatory m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
49
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(58 citation statements)
references
References 27 publications
2
49
1
Order By: Relevance
“…The overall impact may have been masked by lack of effect for the children in the intervention group who did not directly benefit from the intervention, highlighting the increasingly cited issue of trial design for an intervention where a benefit is only required, sought or gained by a limited proportion of the intervention population 46 47. The nature of the intervention (treatment of symptomatic children) is such that there are no immediate benefits in terms of reduced transmission for the wider group, of one individual taking up the intervention, such as there might be with an intervention such as intermittent screening and treatment or intermittent preventive treatment 18. The increased absenteeism attributed to illness observed in the intervention group during spot checks was unexpected but could potentially be explained by factors related to the intervention design.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The overall impact may have been masked by lack of effect for the children in the intervention group who did not directly benefit from the intervention, highlighting the increasingly cited issue of trial design for an intervention where a benefit is only required, sought or gained by a limited proportion of the intervention population 46 47. The nature of the intervention (treatment of symptomatic children) is such that there are no immediate benefits in terms of reduced transmission for the wider group, of one individual taking up the intervention, such as there might be with an intervention such as intermittent screening and treatment or intermittent preventive treatment 18. The increased absenteeism attributed to illness observed in the intervention group during spot checks was unexpected but could potentially be explained by factors related to the intervention design.…”
Section: Discussionmentioning
confidence: 99%
“…A 2017 review described a range of strategies aimed at reducing the burden of malaria among school-aged children,15 16 including using antimalarial drugs for prevention, as well as case management within the school context 7 17 18. Case management evaluations in Ghana, Malawi and Tanzania demonstrated teachers can effectively deliver presumptive malaria treatment in schools 19–21.…”
Section: Introductionmentioning
confidence: 99%
“…The malaria burden in school-aged children has been underappreciated, 6 but a wealth of evidence from Uganda and elsewhere suggests that IPT of malaria in schoolchildren provides substantial health benefits and might improve cognitive function. 7 , 8 , 9 , 10 Additionally, parasite prevalence is typically highest in school-aged children (although age ranges vary with transmission intensity), who serve as reservoirs of infection for the onward transmission of malaria to mosquitoes. 11 Targeted use of chemoprevention in school-aged children will benefit individual children 7 and might decrease malaria transmission by reducing the infectious reservoir, which would benefit the community.…”
Section: Introductionmentioning
confidence: 99%
“…In settings with highly seasonal malaria transmission, treatment at the end of the transmission season leads to prolonged parasite free time making the timing of the distribution critical. 21 In Malawi, annual NTD MDA occurs in April, which is also the end of the malaria high transmission season. However, on-going transmission throughout the year may make this timing less critical than the frequency of distributions.…”
Section: Discussionmentioning
confidence: 99%
“… 13 15 Clinical trials have shown benefits of school-based mass treatment of malaria, including decreased Plasmodium falciparum prevalence, incidence of clinical malaria, and prevalence of anemia. 8 , 16 21 …”
Section: Introductionmentioning
confidence: 99%